CardinalKit: open-source standards-based, interoperable mobile development platform to help translate the promise of digital health - Aalami, Oliver; Hittle, Mike; Ravi, Vishnu; Griffin, Ashley; Schmiedmayer, Paul; Shenoy, Varun; Gutierrez, Santiago; Venook, Ross (JAMIA open, 2023)
Abstract Smartphone devices capable of monitoring users’ health, physiology, activity, and environment revolutionize care delivery, medical research, and remote patient monitoring. Such devices, laden with clinical-grade sensors and cloud connectivity, allow clinicians, researchers, and patients to monitor health longitudinally, passively, and persistently, shifting the paradigm of care and research from low-resolution, intermittent, and discrete to one of persistent, continuous, and high resolution. The collection, transmission, and storage of sensitive health data using mobile devices presents unique challenges that serve as significant barriers to entry for care providers and researchers alike. Compliance with standards like HIPAA and GDPR requires unique skills and practices. These requirements make off-the-shelf technologies insufficient for use in the digital health space. As a result, budget, timeline, talent, and resource constraints are the largest barriers to new digital technologies. The CardinalKit platform is an open-source project addressing these challenges by focusing on reducing these barriers and accelerating the innovation, adoption, and use of digital health technologies. CardinalKit provides a mobile template application and web dashboard to enable an interoperable foundation for developing digital health applications. We demonstrate the applicability of CardinalKit to a wide variety of digital health applications across 18 innovative digital health prototypes. Lay Summary The 21st Century Cures Act has mandated data interoperability and also defined the business rules and mechanisms to do so. It is now incumbent upon us to develop the tools to access these exposed application programming interfaces to improve the delivery of health care in the United States. We review the current landscape for open-source frameworks to develop patient-facing mobile applications and also present CardinalKit as an open-source standards-based mobile development platform for researchers and health systems to leverage. We are at a turning point and a rise of great opportunities to improve the healthcare experience.